028 Determining the effect of objective and subjective criteria on a risk assessment tool in a Children's Emergency Department. (14th September 2011) - Roland, D; Davies, F; Lewis, G
Abstract : Objectives and Background: Children with serious illness can be difficult to spot, especially for non-experienced staff. Although adult "early warning scores" are now commonly used in Emergency Departments (ED), there is no such system for children. The Paediatric Observation Priority Score (POPS) is a physiological and observational scoring system (range 0–16) designed for use by healthcare professionals of varying clinical experience at initial assessment in our ED. The aim is to use POPS to identify sick children, aid healthcare professionals in confidently discharging or re-directing patients and providing a departmental level of acuity to aid resource allocation. A first phase of the validation process examined the utility of the more subjective criteria of POPS (level of alertness, work of breathing, nursing concern and relevant background history) against the physiological criteria (heart rate, breathing rate, saturations and temperature) in determining admission to the children's hospital assessment unit from the ED. Methods: Convenience sample case note review of attendances to the ED, analysing patient discharge disposition against initial POPS recorded. Results: 942 (injuries not included) presentations from 2009 to 2010 were included in the study with an overall admission rate of 36% (339/942). RR of admission of admission with a POPS of >0 was 2.1 (CI 1.6 to 2.7). Conclusion: The large range of confounding influences affecting the admission of children to hospital makes an initial point of care assessment predictive model difficult. This work demonstrated interesting variation in performance of the component sections of the POPS score. The use of subjective, user dependant factors, may inhibit the performance of physiological values which have traditionally be used in aiding illness recognition. Further work is ongoing to improve the performance of the tool as an adjunct to risk assessment and resource allocation.